The use of cultured cells with defects of citrulline metabolism in diagnosis and in the study of intercellular communication - Davidson, James Schonland (Division of Chemical Pathology, 2018)
Citrullinemia and argininosuccinic aciduria are two disorders resulting from defects in two consecutive enzymes of the urea cycle, argininosuccinate synthetase and argininosuccinate lyase. Fibroblast cell lines were derived from patients with these disorders and the diagnoses, which had been made on the basis of amino acid levels in plasma and urine, were confirmed by demonstrating that the cell lines were unable to incorporate 14 c-citrulline into protein. DNA from the argininosuccinate synthetase-deficient (ASS⁻) cells was analysed by restriction enzyme digestion and hybridisation to a cDNA probe which had been cloned from human argininosuccinate synthetase mRNA. No defect in the patient's DNA could be demonstrated, indicating that no major deletions in the argininosuccinate synthetase genes were present in this patient. Co-cultures of the ASS⁻ and argininosuccinate lyase-deficient (ASL⁻) fibroblasts were able to incorporate 14 citrulline into protein at rates comparable to normal fibroblasts. This complementation did not require cell fusion, was dependent on cell contact, and was not the result of exchange of metabolites or enzymes via the culture medium. These results indicated that complementation occurred by the exchange of metabolites via intercellular junctions between the two cell types. Co-cultures of ASS⁻ and ASL⁻ cells were used as an assay system for measuring intercellular junctional communication. This allowed quantitation of the effects of pH and extracellular divalent cations on junctional communication. Tumor promoters such as phorbol esters and organochlorine pesticides have been reported to inhibit intercellular junctional communication in other systems, and this inhibitory activity may be related to the mechanism of tumor promotion. The organochlorine pesticide 1,1,1-trichloro- 2,2-bis(p-chlorophenyl)ethane (DDT) was shown to be an inhibitor of junctional communication in ASS⁻/ASL⁻ cocultures. This inhibition was reversible, of rapid onset, and independent of extracellular calcium. The tumor-promoting phorbol ester 12-0-tetradecanoyl-phorbol-13- acetate (TPA) also rapidly induced inhibition of junctional communication. However, co-cultures between Chinese hamster V79 cells, which are deficient in ASS⁻, and ASL⁻ human fibroblasts were more sensitive to inhibition by TPA than the original ASS⁻/ASL⁻ co-cultures. Refractoriness to TPA occurred following prolonged treatment with high concentrations of TPA. Retinoic acid and other retinoids also inhibited junctional communication, and the inhibitory effects of retinoic acid and TPA were additive. The significance of these results in relation to the anti-tumor-promoting activity of retinoic acid is discussed. It is concluded that co-cultures of ASS⁻ and ASL⁻ cells constitute a useful system for providing quantitative measurements of intercellular junctional communication under a wide range of experimental conditions.